Ergodicity with respect to the spatial variable of discrete-time stochastic flows - Glinyanaya, E. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
We consider a discrete-time flow of particles in the random environment and investigate spatial properties for such flow at a fixed moment of time. Results about the stationarity and ergodicity of the flow are obtained.